2016
DOI: 10.1089/jir.2016.0031
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Expression of Transcription Factors in Response to Interferonβ and Interferonλ1

Abstract: After viral infection, type I and III interferons (IFNs) are coexpressed by respiratory epithelial cells (RECs) and activate the ISGF3 transcription factor (TF) complex to induce expression of a cell-specific set of interferon-stimulated genes (ISGs). Type I and III IFNs share a canonical signaling pathway, suggesting that they are redundant. Animal and in vitro models, however, have shown that they are not redundant. Because TFs dictate cellular phenotype and function, we hypothesized that focusing on TF-ISG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 73 publications
3
19
0
1
Order By: Relevance
“…Recent evidence, however, supports non-redundant functional roles for each, particularly at sub-saturating levels, which are likely more relevant to initial exposure of the respiratory mucosa to small doses of a viral pathogen contained in micro-droplets. For example, sub-saturating combinations of IFN-β and IFN-λ1 synergize towards suppression of vesicular stomatitis virus in vitro (Voigt and Yin, 2015), and additively enhance and sustain expression of many ISGs (Novatt et al, 2016). In RSV infection of MDDCs, using B18R to block type I IFNs (Figure 5), we have shown that the majority of ISG induction relies on the presence of type I IFNs, however this does not exclude the possibility that optimal ISG expression requires -α, -β and -λ IFNs in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence, however, supports non-redundant functional roles for each, particularly at sub-saturating levels, which are likely more relevant to initial exposure of the respiratory mucosa to small doses of a viral pathogen contained in micro-droplets. For example, sub-saturating combinations of IFN-β and IFN-λ1 synergize towards suppression of vesicular stomatitis virus in vitro (Voigt and Yin, 2015), and additively enhance and sustain expression of many ISGs (Novatt et al, 2016). In RSV infection of MDDCs, using B18R to block type I IFNs (Figure 5), we have shown that the majority of ISG induction relies on the presence of type I IFNs, however this does not exclude the possibility that optimal ISG expression requires -α, -β and -λ IFNs in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we considered coefficient of variation from 0.3 to 1.5 to reflect typically measured values 43 . Importantly, the model is in line with the present biochemical knowledge 14 , 37 by allowing the only difference in responses to arise from the different kinetics of both receptor complexes. We quantified the difference in receptor kinetics using the ratio of deactivation rates of the type III and type I receptor complexes, and , respectively (see Sections 3.2–3.3 of SI), which we call the differential kinetics coefficient.…”
Section: Resultsmentioning
confidence: 66%
“…The mechanism that explains the differential physiological effect of IFN- α and IFN- λ 1 despite inducing the same signaling effectors is largely unknown 12 14 . Recent data 12 14 , 37 , however, support the hypothesis that a differential temporal profile, understood as time series of the copy numbers of nuclear p-STAT1/1 homodimers and p-STAT1/2 heterodimers, carries information about identity and quantity of both IFNs and is further propagated by the gene expression machinery into distinct physiological responses. For instance, western blot experiments show a prolonged phosphorylation in response to IFN- λ 1 compared to IFN- α 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, IL-33 and sST2 transcript correlated with IRF-1 mRNA levels, which was found to be essential for IL-33 production under viral infections in endothelial cells ( 95 ). Type I and II IFNs regulate IRF-1 expression in different cells ( 43 , 96 , 97 ), suggesting a possible indirect regulation of IL-33 expression by IFNs highlighting the need to further investigate the link between IL-33/ST2 axis and IFNs in the context of CD.…”
Section: Discussionmentioning
confidence: 99%